English mediopassive constructions: a cognitive, corpus-based study of their origin, spread, and current status - Hundt, Marianne (Language and computers, 2010)
List of tables and figures; Preface; Chapter 1. Introduction; Chapter 2. Defining the object of study; Chapter 3. Previous studies; Chapter 4. Theoretical background; Chapter 5. The mediopassive in Present Day English; Chapter 6. The history of mediopassives; Chapter 7. Conclusion; References; Appendix 1. Primary material; Appendix 2. Sample pages of Sears & Roebucks catalogues; Appendix 3. Additional tables and figures; Index.